The Dermacentor (Acari, Ixodida, ixodidae) of Mexico: Hosts, geographical distribution and new records - Guzmán Cornejo, Carmen (2016)
Distribution and host data from published literature and previously unpublished collection records are provided for all nine species of the Holarctic tick genus Dermacentor that are known to occur in Mexico, as well as two species that may occur there. Parasite-host and host-parasite lists are presented, together with a gazetteer of collection localities and their geographical coordinates.